Differentiated thyroid carcinomas associated with chronic thyroiditis: biological and clinical properties - Myshunina, T.M.; Guda, B.D.; Bolgov, M.Yu.; Mikhailenko, N.I.; Tronko, N.D. (Experimental Oncology, 2018)
Aim: To determine biological and clinical features of papillary and follicular thyroid carcinomas associated or not associated with chronic thyroiditis. Materials and Methods: The study was conducted by retrospective analysis of medical histories of 2,459 patients with thyroid cancer. Tumor size, its category according to the TNM system, multi-focal properties of tumor growth, carcinoma invasiveness, as well as disease stage, rates of relapses and metastasis, and also cumulative survival rates were analyzed. Results: The tumor size in patients with papillary or follicular carcinoma associated with thyroiditis was smaller compared to the patients without thyroiditis. In the first case, the invasion frequency into extrathyroid structure and into the capsule was also lower. Multi-focal growth of both carcinoma types was registered more frequently in the presence of thyroiditis. The frequency of papillary carcinoma metastasis to lateral cervical lymph nodes was lower in the presence of thyroiditis, the frequency being equal for metastasis into lymph nodes of the VI lymph outflow zone in both groups of patients (with and without thyroiditis). In the presence of thyroiditis, the frequency of distant papillary carcinoma metastasis was decreased, no metastases were detected in patients with follicular carcinoma. In the group of patients with papillary carcinoma there was found no relation between the presence of thyroiditis and disease stage, relapse rates, and mortality levels; however, the risk of follicular carcinoma relapse was significantly lower in patients with thyroiditis. Conclusions: The presence of chronic thyroiditis in papillary carcinoma patients showed a certain positive impact on the course of the disease, in particular, primary tumor growth, invasion, and metastasis. Such effect is even more expressed in the patients with follicular thyroid carcinoma. Key Words: papillary and follicular thyroid carcinomas, autoimmune thyroiditis.